Development of the Solar EUV Telescope Engineering Model for a Satellite - Sun-Min Lee; Min-Hwan Jang; Eun-Seok Park (Journal of Astronomy and Space Sciences, 2003)
The aim of this paper is to describe the results of the study on the extreme-ultra-violet (EUV) solar telescope, which is designed for a possible satellite mission. Since the EUV band can not be observed on the ground, the observation in EUV should be performed in space using a satellite or a rocket. Design of the Extreme-Ultra-Violet solar Telescope (EUVT) in this study is based on ``Designing a small-sized engineering model of solar EUV telescope for a Korean satellite" (Han et al. 2001). Our EUVT design is satisfied with the requirements for a satellite in size and input voltage. The major goal of the study is to confirm if we can detect the specific wavelength (58.4nm to 62.9nm) with the EUVT. We describe re-designing of the EUVT to decrease a shelter ratio. Also we describe the technics in the optic system and the detector, which were used to manufacture the EUVT. We explain the detective program, which is to calculate the amount of the solar radiation, and the image data processing system.